PENGARUH KOMPENSASI FINANSIAL DAN PENGAWASAN PIMPINAN TERHADAP DISIPLIN KERJA KARYAWAN PADA DIVISI PERALATAN PT. STATIKA MITRASARANA PADANG - Riani Elita Putri; Menik Kurnia Siwi (Universitas Negeri Padang, 2018)
This study aims to determine and prove how much is the influence of Financial Compensation and Leaders Supervision on Employees’ Discipline of Equipment Division PT.Statika Mitrasarana Padang. The type of research was causative. Population in this research was all employees at division of equipment of PT. Statika Mitrasarana Padang. Since the number of samples of this study were less than 100 people, population research method was used. Therefore, the samples on this study were the entire number of population that was as much as 42 respondents. The type of data used was secondary and primary obtained through the distribution of questionnaires to employees. The analytical method used was descriptive analysis and quantitative through multiple regression using SPSS version 15.00. The results of this study indicate that, (1) Financial Compensation has a positive and significant effect on employees’ work discipline in equipment division of PT. Statika Mitrasarana, (2) Control of Leader have a positive and insignificant effect to work discipline of employees at division of equipment of PT. Statika Mitrasarana. The results of this study will be recommended to several related parties, among others for PT. Statika Mitrasarana Padang can improve and maintaining the discipline of its employees for the development of the company and for other researchers as a reference material that will continue the further research.Keywords: Financial compensation, Leadership supervision, Work discipline